The mdm-2 gene is induced in response to UV light in a p53-dependent manner. - Perry, M E (1993)
Irradiation of mammalian cells with UV light results in a dose-dependent accumulation of the p53 tumor-suppressor gene product that is evident within 2 hr. UV treatment causes a dramatic increase in p53-specific transcriptional transactivation activity and an increase in expression of the p53-responsive gene mdm-2. UV-stimulated mdm-2 expression is not directly correlated with the level of p53 protein in a cell because mdm-2 induction is delayed at high UV doses even though p53 levels rise almost immediately. Cells lacking p53 protein do not respond to UV by increasing their expression of mdm-2. The delayed induction of mdm-2 at high UV doses suggests that, in addition to p53 protein levels, other factors contribute to the regulation of mdm-2 expression following UV treatment. The time of induction of mdm-2 in cells treated with UV light correlates with recovery of normal rates of DNA synthesis, presumably after DNA repair. These data indicate a possible role for mdm-2 in cell cycle progression.